ORGANIZAREA ŞI DESĂVÂRŞIREA INSTRUIRII ŞI EDUCAŢIEI ECOLOGICE A STUDENŢILOR DIN UNIVERSITĂŢILE REPUBLICII UNDE BIOLOGIA ESTE DISCIPLINĂ GENERALĂ (SFÂRŞITUL SEC.XX-ÎNCEPUTUL SEC.XXI) - USM ADMIN (Moldova State University, 2007)
The finalities of the national system of education, reformed at the end of the last century anticipate the priority of the general human values which include different aspects of the human culture where the leading place, along with the culture of working and intellect, is placed the ecological culture of the future specialist. The formation of the ecological culture is an interdisciplinary problem and requires not only the analytical programs consummated at the all disciplines, the corresponding theoretical-practical training of the teaching staff, but also of courses of summarizing on the problem, with the specific features of the concrete specialties.